"Adults talk too much": Intergenerational dialogue and power in the Peruvian movement of working children. (November 2015) - Taft, Jessica K
Recent work on children's participatory rights has suggested the need to pay attention to adult–child relationships and foster intergenerational dialogue. Drawing on ethnographic observation and in-depth interviews with the Peruvian movement of working children, this article explores the ambiguous and complex status of adult voice in organizations that have taken up children's participation. The ideal of egalitarian intergenerational collaboration is incredibly difficult to implement given the broader social context of age-based inequality. Despite good intentions and a deep commitment to children's agency and authority, adults and children in this movement continue to replicate deeply structured patterns of behavior that give adults greater power.